The Geographical Location and Its Impact on the History of Libya (Journal of human and social sciences, 2024)
This study examines the impact of Libya's geographical location on its historical, economic, and cultural development. It reviews the strategic importance of Libya's position in the Mediterranean basin and ancient trade routes, illustrating how this location served as a bridge for cultural and commercial exchange between Africa and Europe. The study also addresses the challenges and opportunities provided by this location in the modern era.
Keywords: Geographical location; history of Libya; trade routes; Mediterranean; cultural exchange